Histological analysis of pre-transplant deceased donor renal biopsies and its association with long-term graft survival and function - Karla Pegas; Roger Kist; Cynthia Keitel; Larissa Pacheco Larissa Pacheco; Eduardo Cambruzzi; Elizete Keitel (Society of Diabetic Nephropathy Prevention, 2018)
Background: Pre-implantation kidney biopsy is a diagnostic tool used for deciding whether to accept an expanded-criteria deceased donor graft. However, the study of histopathological lesions in renal compartments as prognostic factors for graft function and survival has led to conflicting results. Objectives: This study aimed to evaluate the presence of chronic lesions in pre-implantation kidney biopsies and correlate the findings with graft function and survival at 1, 3, and 5 years post-transplantation. Patients and Methods: Around 430 kidney biopsies from standard and expanded-criteria deceased donors were analyzed between 2006 and 2013 at the hospital Santa Casa de Porto Alegre. Lesions were graded according to the Banff criteria. The glomerular filtration rate (GFR) was calculated by the CKD-EPI equation. Graft survival was calculated by the Kaplan-Meier method. Clinical variables related to graft outcome were assessed by Cox regression analysis. Results: The decrease in graft survival and function at the analyzed periods was related to a greater degree of chronic lesions in renal compartments. Glomerulosclerosis (GS) was an independent risk factor for graft loss. Conclusions: Chronic lesions in any renal compartment should be taken into account in the clinical decision of accepting the kidney, but a greater weight should be given to GS. Kidney recipients with more than 25% GS had a less favorable outcome in our study